2014
DOI: 10.1152/ajpendo.00308.2013
|View full text |Cite
|
Sign up to set email alerts
|

The identification of irisin in human cerebrospinal fluid: influence of adiposity, metabolic markers, and gestational diabetes

Abstract: eral action of irisin improves glucose homeostasis and increases energy expenditure, with no data on a central role of irisin in metabolism. These studies sought to examine 1) presence of irisin in human cerebrospinal fluid (CSF) and banked human hypothalamic tissue, 2) serum irisin in maternal subjects across varying adiposities with or without gestational diabetes (GDM), and 3) their respective neonate offspring. CSF, serum, and neonatal cord serum were collected from 91 pregnant women with and without GDM a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(120 citation statements)
references
References 38 publications
10
106
2
2
Order By: Relevance
“…As a large range of circulating irisin was detected by the current reports [5][6][7][8], Fig. 2 The differences of circulating irisin between participants with GDM and healthy control groups There has been only one report, plus ours, that mentioned when GDM was diagnosed [5], and only two studies reported how the patients were treated [5,7].…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…As a large range of circulating irisin was detected by the current reports [5][6][7][8], Fig. 2 The differences of circulating irisin between participants with GDM and healthy control groups There has been only one report, plus ours, that mentioned when GDM was diagnosed [5], and only two studies reported how the patients were treated [5,7].…”
Section: Discussionmentioning
confidence: 57%
“…If heterogeneity was not 1703. 3 (1354.8-2097.9) ng/mL vs. 1873.8 (1519.8-2294.8) ng/mL, P=0.01) [7], whereas Piya et al did not support this finding (GDM 802±88 ng/mL vs. healthy control 805±53 ng/mL) [8]. These controversial results might mostly be due to the small number of sample sizes, which could affect the power of statistical analysis conducted.…”
Section: Discussionmentioning
confidence: 93%
“…To the best of our knowledge, only five studies on the association between irisin and GDM have been reported in the literature [8][9][10][11][12]. In light of the conflicting results of these studies, we also wished to investigate this topic.…”
Section: Objectivementioning
confidence: 99%
“…As determined in various studies, serum irisin levels decrease in type 2 diabetes mellitus (DM) and gestational DM, non-alcoholic hepatic failure and in individuals with lower body mass indices vs. obese individuals and increase in metabolic syndrome (14,(20)(21)(22)(23).…”
Section: Discussionmentioning
confidence: 99%